Property-led development als neuer Ansatz in der Stadtentwicklung? Das Beispiel der South Boston Waterfront in Boston - Heeg, Susanne (ERDKUNDE, 2008)
In many cities, property-led development seems to be an attractive and practicable strategy in order to enhance socioeconomic growth. Cities boost with attractive investment environments and locations in large-scale redevelopments in order to attract external investors and affluent households. Urban development projects are part and parcel of strategies to gain a favourable position in the urban competition. However, this goes along with the attempt to guarantee favourable investment conditions in order to convince project developer and investors to realize buildings. This implies variances in zoning and urban planning and tax incentives which absorb speculative risks of the developers. This urban development strategy is analyzed in the context of a shift towards entrepreneurialism and new forms of urban governance. The case study to support the argument is the South Boston Waterfront, a large-scale redevelopment project in Boston.